Physical performance tests, self-reported outcomes, and accidental falls before and after total knee arthroplasty: An exploratory study. (August 2013) - Swinkels, Annette; Allain, Theresa J.
<x xml:space="preserve">Abstract</x> This longitudinal, observational study explored the relationship between physical performance tests, self-reported outcomes, and accidental falling, before and after total knee arthroplasty (TKA). Thirty-seven patients were randomly selected from a larger study of falling before and after surgery conducted at a UK National Health Service Orthopaedic Unit. Physical performance tests were the Berg Balance Score (BBS), Timed Up and Go (TUG), and Hand Grip Strength (HGS). Self-reported outcomes incorporated the Western Ontario and McMaster's Osteoarthritis Index (WOMAC), Activities Balance Confidence Scale (ABC-UK), Geriatric Depression Scale (GDS), and accidental falls. Paired pre- and postoperative data were available on 22 patients. A total of 22.7% patients fell before and after TKA. Postoperative improvement in BBS and TUG was found in 41% and 50% of patients, respectively, HGS did not change. BBS showed a consistent moderate-to-strong association with other physical tests both before and after surgery; TUG (rs −0.76; rs −0.90), maximal HGS (r 0.49; r 0.48), and self-report measures; ABC-UK (r 0.52; r 0.74), WOMAC stiffness (r −0.53; r −0.48), and WOMAC function (r −0.56; r −0.45). Although self-report questionnaires are an efficient, cost-effective approach to outcome assessment in TKA, there is a growing case for inclusion of physical performance tests. The Berg Balance Score may be a useful addition to outcome assessment in patients with TKA.